1989
DOI: 10.1021/bi00437a053
|View full text |Cite
|
Sign up to set email alerts
|

Proton nuclear magnetic resonance study of the molecular and electronic structure of the heme cavity in Aplysia cyanometmyoglobin

Abstract: The 1H NMR spectrum of the low-spin, cyanide-ligated ferric complex of the myoglobin from the mollusc Aplysia limacina has been investigated. All of the resolved resonances from both the hemin and the proximal histidine have been assigned by a combination of isotope labeling, spin decoupling, analysis of differential paramagnetic relaxation, and nuclear Overhauser (NOE) experiments. The pattern of the heme contact shifts is unprecedented for low-spin ferric hemoproteins in exhibiting minimal rhombic asymmetry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Heme Orientational Heterogeneity-1 H NMR spectra for both metMb (51) and metMbCN (19,20) had shown that in solution, ϳ20 -25% of the globin possesses a heme rotated 180°about the ␣,␥-meso axis with respect to the unique orientation reported in the crystal structure (12) (shown in Fig. 1).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Heme Orientational Heterogeneity-1 H NMR spectra for both metMb (51) and metMbCN (19,20) had shown that in solution, ϳ20 -25% of the globin possesses a heme rotated 180°about the ␣,␥-meso axis with respect to the unique orientation reported in the crystal structure (12) (shown in Fig. 1).…”
Section: Resultsmentioning
confidence: 82%
“…Hyperfine shifts reflect electronic and/or magnetic properties of the chromophore, and hence can be extraordinarily sensitive to (and hence render detectable) small structural changes that are unlikely to be detected in either a crystal structure or a solution NMR structure of a diamagnetic analog. Perhaps the best examples of the exquisite sensitivity are the observation of isotope effects on iron-porphyrin covalency due to the distal H-bond to the bound ligand (16 -18) and the characterization of small populations of globins with alternate orientation of the heme about the ␣,␥-meso axis (19,20).…”
Section: Myoglobin (Mb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Minor Component-Sufficient assignments are pursued in order to establish whether the minor component (ϳ40%) arises from the heme reoriented 180°about the ␣,␥-meso axis (30,31), from another polypeptide chain (isoform), or from damage or modification during isolation. The upfield TOCSY map reveals three minor component methyl peaks (labeled X 2 , X 3 , and X 4 in Fig.…”
Section: Samplementioning
confidence: 99%
“…Detailed methyl assignments confirm these expectations in all published 'H-NMR spectra For an axial imidazole orientation with its projection bisecting the N-Fe-N vector (C in Fig.l), the methyl contact shift asymmetry is expected to collapse and lead to very similar contact shifts for all four methyls, with the asymmetry dominated by the smaller local peripheral perturbations. Indeed, recent X-ray data have shown that Aplysia Mb possesses an axial histidyl imidazole oriented with a projection passing closer to the meso position than the pyrroles [58] and 'H-NMR resonance assignments of the cyano-met Mb complex reveal strongly reduced electron asymmetry and very similar shifts for the four methyls [59]. Thus the methyl contact shift pattern indicates that the major rhombic perturbation originates on a vector more closely bisecting the N-Fe-N axis rather than along either axis.…”
Section: Heme Ma~neticlclectronic Structurementioning
confidence: 99%